Pendekatan Whole Word dan Strategi VAKT untuk Mengembangkan Keterampilan Fungsional Membaca dan Menulis Permulaan pada Anak dengan Retardasi Mental Ringan - Diana Dwi Jayanti (JCE (Journal of Childhood Education), 2018)
This qualitative case study aimed to develop the functional reading and writing skills of mild mentally retarded children through whole word approach and VAKT strategy. The subject in this study was selected through the procedures of subject determination in qualitative research proposed by Sarantakos (1993, in Poerwandari 2005), namely: 1) not directed to the large number of participants but in typical cases according to the specificity of the research problem, 2) not directed to representation in terms of numbers or random events, but to context matches. Based on the above explanation, the researcher then determined the general criteria of the subjects / participants of the study as follows: 1) Subjects were children aged between 6-8 years old who were in kindergarten (group B) or elementary school (first grade or second grade), 2) subjects were children with mild mental retardation who have difficulty in developing functional reading and writing skills. Methods of data collection in this study were conducted through observation, interviews, and informal assessments, as well as documentation of field notes during data mining. Data analysis was performed by comparing the initial condition of the subject before stimulation implemented with the final condition of the subject after the stimulation completed. The results of data analysis indicated that the whole-word approach and VAKT strategy can be applied to develop the early functional reading and writing skills in children with mild mental retardation